KEPUASAN KERJA MEMEDIASI FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN PT. X - PARAMITHA, TALITHA HANUNSAKHA; RUSWIDIONO, WASISTO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This study aims to test job satisfaction in mediating factors that affect employee performance. Employee performance is one of the important things in the company. The object in this study is PT. X. This form of research uses descriptive research and uses purposive sampling techniques of 60 employees. Data collection was carried out by distributing questionnaires to respondents and using Likert scales. Data analysis method carried out using SEM-PLS. The results of this study show that occupational health and safety variables have no effect on employee performance, the work environment does not affect employee performance, but occupational health and safety affects job satisfaction, work environment affects job satisfaction, job satisfaction affects employee performance, shows that job satisfaction can mediate the relationship between occupational health and safety on employee performance, and job satisfaction can mediate the relationship between the work environment and employee performance.